Sosialisasi Pemanfaatan Telefarmasi Dan Edukasi Penyakit Menular Seksual Di Puskesmas Narmada - Lalu M. Rifqi Azami S; Silhiyatun Mayada; Fara Mutia Bimantika; Mahacita Andanalusia; Yoga Dwi Saputra; Azizatul Adni; I Wayan Agus Arimbawa (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Sexually transmitted infections remain a major public health issue in West Nusa Tenggara, driven by limited awareness and access to accurate information. This community service program aimed to improve public understanding of telepharmacy and STI prevention through participatory education at Narmada Public Health Center. A total of 25 participants engaged in telepharmacy education, distribution of STI educational leaflets, and training on using a digital health information website. The participatory approach enhanced engagement, digital literacy, and comprehension of preventive health messages. Overall, the activities effectively strengthened community readiness to access telepharmacy services and utilize digital resources for STI prevention.